Bye-Bye Dementia: Prevent dementia in the elderly with brain gym - Nourmayansa Vidya Anggraini; Diah Ratnawati; Ritanti Ritanti; Sang Ayu Made Adyani; Chandra Tri Wahyudi; Nirmala Nirmala; Sulistya Nur’aeni Wisudawati; Nadia Shahidda; Farah Aprilia (Universitas Muhammadiyah Magelang, 2024)
Elderly individuals often encounter various health issues, including mental and psychological decline such as dementia. One solution to address this is through brain gym therapy. The aim of this community service is to enhance the knowledge of the elderly regarding dementia, improve their ability to perform brain gym exercises, and observe the effects on their blood pressure levels. Counseling and interventions were conducted with 25 participants aged over 45 years residing in RT 03/RW 05, Limo Village, Depok. Educational methods included lectures, distribution of educational leaflets, and demonstrations of brain gym. This service successfully increased the elderly's knowledge about dementia, with the majority scoring between 51-100, comprising 14 individuals (56%). Additionally, there was a decrease in the average systolic and diastolic blood pressure levels.